Three-Dimensional Imaging of the Developing Human Fetal Urogenital-Genital Tract: Indifferent Stage to Male and Female Differentiation() - Isaacson, Dylan (Differentiation, 2018)
Recent studies in our lab have utilized three imaging techniques to visualize the developing human fetal urogenital tract in three dimensions: optical projection tomography, scanning electron microscopy and light sheet fluorescence microscopy. We have applied these technologies to examine changes in morphology and differential gene expression in developing human external genital specimens from the ambisexual stage (<9 weeks fetal age) to well differentiated male and female organs (>13 weeks fetal age). This work outlines the history and function of each of these three imaging modalities, our methods to prepare specimens for each and the novel findings we have produced thus far. We believe the images in this paper of human fetal urogenital organs produced using light sheet fluorescence microscopy are the first published to date.